Taste receptors affect male reproduction by influencing steroid synthesis - Wenjiao Liu; Wenjiao Liu; Wenjiao Liu; Ting Gong; Ting Gong; Ting Gong; Fangxiong Shi; Houqiang Xu; Houqiang Xu; Houqiang Xu; Xiang Chen; Xiang Chen; et al. (Frontiers in Cell and Developmental Biology, 2022)
For the male genetic materials to reach and fertilize the egg, spermatozoa must contend with numerous environmental changes in a complex and highly sophisticated process from generation in the testis, and maturation in the epididymis to capacitation and fertilization. Taste is an ancient chemical sense that has an essential role in the animal’s response to carbohydrates in the external environment and is involved in the body’s energy perception. In recent years, numerous studies have confirmed that taste signaling factors (taste receptor families 1, 2 and their downstream molecules, Gα and PLCβ2) are distributed in testes and epididymis tissues outside the oral cavity. Their functions are directly linked to spermatogenesis, maturation, and fertilization, which are potential targets for regulating male reproduction. However, the specific signaling mechanisms of the taste receptors during these processes remain unknown. Herein, we review published literature and experimental results from our group to establish the underlying signaling mechanism in which the taste receptor factors influence testosterone synthesis in the male reproduction.